Experimental and Discrete Element Method Analysis of Galvanized Steel Scrap Particles Along and After an Inclined Chute. Issue 8 (4th April 2022) - Georgakopoulos, Evangelos; Hosseini, Ashkan; Kerry, Timothy; Hage, Johannes; Meijer, Koen; Offerman, Erik; Yang, Yongxiang
Abstract : HIsarna is a novel ironmaking process with great raw materials versatility that is attractive for various secondary resources. Among the materials that can be recycled, there is steel scrap which is fed to the furnace bath through an inclined chute. The velocity distribution of the scrap particles along the chute affects the particles' distribution on the liquid slag and, thereupon, the efficient operation of the reactor. In this study, the flow of steel scrap particles along an inclined chute with the same dimensions as those of the actual chute of the HIsarna plant is investigated experimentally and numerically. The simulations are validated using chute tip velocity and mass fractions collected at the different compartments of a sampling device. Translational and angular velocity distributions along and across the chute are reported, and the effect of different parameters are investigated. The impact of the shape of the particles on the simulation process is found to be negligible. The angular velocity distribution in cross‐sections of the chute exhibited a V‐shaped orientation, whereas the translational velocity displayed similar values across the cross‐sections. Moreover, translational velocity appeared to increase with increasing inclination angles, whereas angular velocity increased with decreasing batch size. Abstract : The shape of scrap particles has a minor effect on the mean tip linear velocity, cross‐sectional profiles along the chute, and particle mass fraction inside the sampling box. The shape of particles affect, the tip and cross‐sectional angular velocity. A higher inclination angle leads to lower tip velocity and profiles. The developed model also is in agreement with experimental findings.